The Institutional Repositioning of the Tax Court Post-Constitutional Court Decision Number 26/PUU-XXI/2023 - Juwari Eddy Winarto; Bambang Soesatyo (Ridwan Institute, 2026)
Article 5 paragraphs (1) and (2) of Law Number 14 of 2002 concerning the Tax Court provides that: (1) technical judicial supervision of the Tax Court is carried out by the Supreme Court; and (2) organizational, administrative, and financial management of the Tax Court is carried out by the Ministry of Finance. As a result, the oversight of the Tax Court operates under a dual oversight system (two-roof system). The Constitutional Court Decision Number 26/PUU-XXI/2023, dated May 25, 2023, represents a significant milestone in the development of constitutional law and tax law in Indonesia. This ruling asserts that the organizational, administrative, and financial management of the Tax Court under the Ministry of Finance is unconstitutional and conflict withs the principle of an independent judiciary as enshrined in the 1945 Constitution of the Republic of Indonesia. According to the Justices, such management must be transferred to the Supreme Court no later than December 31, 2026. This article seeks to analyze and propose the institutional model for the Tax Court following the Constitutional Court's decision specifically, whether the Tax Court will remain a standalone appellate court with the competence to adjudicate tax disputes as it currently exists, or whether it will be integrated into the High Administrative Courts (PT TUN). This article employs a normative legal research method, through statutory, conceptual, and comparative legal methodologies. The research is based on the Tax Court Law, the Administrative Court Law, and the existing judicial framework in Indonesia.